ANALISIS USAHATANI PADI VARIETAS ANAK DARO DI NAGARI CUPAK KABUPATEN SOLOK - Azizah Saria; Lora Triana; Rini Hakimi (Agros Journal of Agriculture Science, 2023)
This research aims to (1) describe the cultivation of the Anak Daro variety of rice in Nagari Cupak, Gunung Talang District, Solok Regency, (2) analyze the income and profits of the Anak Daro variety rice farming in Nagari Cupak, Gunung Talang District, Solok Regency. The research was conducted in May-June 2023 in Nagari Cupak, Gunung Talang District. The research method used was a survey method with direct interviews with farmers guided by a questionnaire. The sample collection method used was simple random sampling with a sample size of 30 Anak Daro rice farmers. The results of the research show that there are cultivation techniques used by farmers that are not in accordance with the rice farming literature. Rice production produced by farmers was 4,555 kg/ha. The average total costs incurred by farmers are IDR 23,182,887/ha/MT, with an average income of IDR 33,400,171/ha/MT, and the profits obtained are IDR 10,217,285/ha/MT. The R/C value is 1.46. From the research results, farmers should pay more attention to cultivation techniques that are in accordance with the literature so that production can be increased, and agricultural extension assistance is needed for farmers. Keywords: Rice farming, anak daro varieties, profits INTISARIPenelitian ini bertujuan untuk (1) mendeskripsikan budidaya tanaman padi varietas anak daro di Nagari Cupak Kecamatan Gunung Talang Kabupaten Solok, (2) menganalisis pendapatan dan keuntungan usahatani padi varietas anak daro di Nagari Cupak Kecamatan Gunung Talang Kabupaten Solok. Penelitian dilakukan pada bulan Mei-Juni 2023 di Nagari Cupak Kecamatan Gunung Talang. Metode penelitian yang digunakan adalah metode survei dengan wawancara langsung kepada petani dengan panduan kuesioner. Metode pengumpulan sampel yang digunakan adalah simple random sampling dengan jumlah sampel 30 orang petani padi jenis anak daro. Hasil penelitian menunjukkan masih ada teknik budidaya yang dilakukan petani yang tidak sesuai dengan dengan literatur usahatani padi. Produksi padi yang dihasilkan petani  sebanyak 4.555 kg/Ha. Total biaya rata-rata yang dikeluarkan petani sebesar   Rp 23.182.887/ha/MT, dengan penerimaan rata-rata sebesar Rp 33.400.171/Ha/MT, dan keuntungan yang didapat sebesar Rp 10.217.285/ha/MT. Nilai R/C senilai 1,46. Dari hasil penelitian, sebaiknya petani lebih memperhatikan teknis budidaya yang sesuai dengan literatur agar produksi dapat ditingkatkan, dan perlu pendampingan penyuluh pertanian bagi petani. Kata Kunci : Usahatani padi, varietas anak daro, keuntungan